PENTINGNYA ASPEK KEAMANAN INFORMASI DATA PASIEN PADA PENERAPAN RME DI PUSKESMAS - Riska Pradita; Retno Kusumo; Rahmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
This study aims to provide socialization about the importance of health data security and information in the implementation of electronic medical records at Puskesmas Botania. Community Service activities were carried out by involving officers through Focus Group Discussions at Puskesmas Botania. The results show that e-Puskesmas has not fulfilled the principles of confidentiality, integrity, and data availability, so it can be accessed by unauthorized parties. In addition, the recording of electronic medical records in e-Puskesmas needs to be improved to facilitate data changes and the availability of health data related to BPJS patient claims. The PkM team recommends the use of individual usernames and passwords, automatic log off feature, network access blocking, data encryption, and integration with the BPJS Health application and data back up process to maintain patient data security.